ROBOTICS ENGINEERING : LEARN IT, TRY IT - Ed Sobey (Oxford : Raintree, 2018)
Have you always been fascinated with robots? Do you want to know how to build one yourself? Learn the basics from a real-life expert and get some hands-on experience. The world of robotics engineering is at your fingertips.
"Dabble lab" --title page.
Includes bibliographical references and index.
Keywords: Robotics -- Juvenile literature; Robotics -- Vocational guidance -- Juvenile literature; Vocational guidance| -- Juvenile literature